An experimental evaluation of Akamai adaptive video streaming over HSDPA networks - Luca De Cicco; Saverio Mascolo; Chaouki Abdallah (2011 IEEE International Symposium on Computer-Aided Control System Design (CACSD), 2011)
Adaptive video streaming is a relevant advancement with respect to classic progressive download streaming such as the one employed by YouTube. Building upon its content delivery network (CDN), Akamai recently started to offer High Definition (HD) adaptive video streaming using HTTP. Nowadays, not only the amount of Internet video traffic is always increasing but also the number of users accessing the Internet using wireless links. In this paper we experimentally investigate the switching algorithm employed by Akamai to implement video quality adaptation over a High Speed Downlink Data Packet Access (HSDPA) link. In order to assess the Quality of Experience we measure goodput, TCP friendliness, and video reproduction continuity. Main results are: 1) Akamai flows are not able to achieve the fair share when competing with a TCP greedy flow due to the conservativeness of the stream-switching algorithm; 2) when the link is shared with a greedy TCP connection in 50% of the experiments the video reproduction was paused for more than 19% of the experiment duration.